Contemporary Regulatory Policy - Eisner, Marc Allen (Lynne Rienner Publishers, 2000)
What is regulation? Why do governments regulate, and how does regulatory change take place? Exploring these and other questions, the second edition of "Contemporary Regulatory Policy" demystifies the field of regulatory politics. Eisner, Worsham, and Ringquist have completely updated their examination of the regulatory process in seven major areas: antitrust, banking and securities, telecommunications, environmental protection, occupational safety and health, consumer products, and energy. They also address the extent to which presidential partisanship, ideological shifts in Congress, and other forces, both within and external to government bureaucracy, influence regulation. Recognizing that no single theory can sufficiently explain regulatory politics, the authors offer students a comprehensive set of tools for navigating recent policy transitions and considering the future direction of US regulation.